Editorial Note - McDonald, Elisabeth (Victoria University of Wellington Law Review, 2014)
The author provides an editorial note to this this special issue of the Victoria University of Wellington Law Review in honour of Harriette Vine, the Faculty’s first woman law graduate. The articles highlight the disparities between women and men in the legal profession, critically analyse aspects of New Zealand law from a feminist perspective, and reflect the impact of gender in judicial decisions or legislation.